STUDI KOMPARASI KECERDASAN EMOSIONAL BERDASARKAN TINGKAT PRESTASI AKADEMIK MAHASISWA PROGRAM STUDI S1 FARMASI UNIVERSITAS SARI MUTIARA INDONESIA - Meliala, Sinarsi; Tobing, Laksana; Ningsih, Siska Dwi; Timoty, Ivan (Psikologi Universitas Sari Mutiara Indonesia, 2022)
Students’ issues in maintaining motivation, dividing study and play time, having no goals, being unable to cope with lecturer pressure, laziness, and other factors such as family environment can be an obstacle in achieving a GPA. GPA, on the other hand, is significant because it can serve as a first impression and a key role in securing employment. As a result, in addition to having great academic intelligence, students must also be able to overcome challenges, understand emotions, and regulate their emotions in order to fully utilize their learning talents. This research is entitled